Optimalisasi Kompetensi Tenaga Pendidik dalam Meningkatkan Kualitas Pembelajaran pada Anak Usia Dini - Yuel Yuel; Oktani Haloho; Joni Saputra; Wirastiani Binti Yusup; Yoan Colina; Silipta Silipta (Institut Nalanda, 2024)
Lack of learning tools is one of the obstacles that is often faced, especially the lack of training related to the curriculum and the minimal availability of teaching aids is a challenge for teachers in AUD units at this time. According to the Principal of PAUD Kasih Bunda, the teacher's teaching and learning process also tends to be monotonous so that learning success is less effective and efficient. In this digital era, it is not uncommon for parents to give AUD access to gadgets which actually have negative effects. The approach used is the Participatory Action Research (PAR) method. As a result of the implementation of community service carried out by the team, the following conclusions were obtained: 1) PAUD educators in Buntut Village, Bali still do not understand and implement quality early childhood education through 9 elements; 2) The strategy of teaching staff in designing, choosing methods, determining techniques and approaches to early childhood learning is very important for developing and honing children's logical thinking abilities. The method chosen must be creative, fun, free from pressure so that it is easy for students to apply.